The Influence of Using Scrambled Pictures to Improve Students’ Ability in Writing Narrative Text of Eleventh Grade Students of SMK Bhakti Utama Bandar Lampung - Novita Uswatun Khasanah (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Most students get difficulties in writing narrative text because in getting the ideas of the story is not easy for them. Therefore, the teacher needs something to stimulate their understanding about narrative text. In this research, the researcher used scrambled pictures as a medium to improve the students’ ability in writing narrative text. The objective of the study is to find out the influence of using scrambled pictures towards the students’ ability in writing narrative text. Related to the research, the researcher used experimental research as the research method. The subjects of the research were the students of two classes (XI KR 1 and XI SM 1) of the eleventh grade students of SMK Bhakti Utama Bandar Lampung in academic year of 2014/2015. The number of the subjects were 40 students and in each class there were 20 students. The pre-test and post-test were given  to those two classes in order to measure the students’ improvement of the ability in writing narrative text. The result showed that the average score of pre-test to post-test of control group (the class who was taught without scrambled pictures) was 52.45 to 63.3. In the experimental group(the class who was taught by using scrambled pictures), the average score of pre-test and post-test was 58.7 to 74.25. From those results, it can be concluded that there was a significance improvement of students’ score in experimental group which was higher than the score in the control class.from the t-test result, it can be seen that the t-value( 4.08) was higher than the p-value (2.02 or 2.71). It indicates that using scrambled pictures can improve their ability in writing narrative text effectively.